1992
DOI: 10.1007/bf00041755
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of resistance to Russian wheat aphid in barley

Abstract: The inheritance of resistance to Russian wheat aphid Diuraphis noxia (Mordvilko), in two resistant barleys, Hordeum vulgare L., ASE/2CM//B76BB and 'Gloria/Come', was studied in the field and in the greenhouse. The resistant genotypes were crossed with susceptible genotypes 'Esperanza' and 'Shyri'. Resistance reactions of F1, BC1, and F2 plants, and individual F2 plant derived F3 families indicated that resistance in each genotype was controlled by the same single dominant gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Several studies have examined the genetics of RWA resistance in barley. Two studies indicated that single dominant or semidominant genes provided RWA resistance in lines from CIMMYT tested with a Mexican RWA population (Robinson et al, 1992) and from Iran tested with RWA from Iran (Assad et al, 1999). Further study indicated that the two CIMMYT lines, derived from the crosses Gloria/Come and ASE/2CM//B76BB, contained the same dominant gene .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have examined the genetics of RWA resistance in barley. Two studies indicated that single dominant or semidominant genes provided RWA resistance in lines from CIMMYT tested with a Mexican RWA population (Robinson et al, 1992) and from Iran tested with RWA from Iran (Assad et al, 1999). Further study indicated that the two CIMMYT lines, derived from the crosses Gloria/Come and ASE/2CM//B76BB, contained the same dominant gene .…”
mentioning
confidence: 99%
“…Two studies indicated that single dominant or semidominant genes provided RWA resistance in lines from CIMMYT tested with a Mexican RWA population (Robinson et al, 1992) and from Iran tested with RWA from Iran (Assad et al, 1999). Two studies indicated that single dominant or semidominant genes provided RWA resistance in lines from CIMMYT tested with a Mexican RWA population (Robinson et al, 1992) and from Iran tested with RWA from Iran (Assad et al, 1999).…”
mentioning
confidence: 99%
“…Genetic analyses of resistance based on biparental mapping populations indicates some lines show dominant single gene resistance to RWA (Robinson et al, 1992; Assad et al, 1999) while others show more complex interactions between multiple additive and dominant genes (Mornhinweg et al, 1995b, 2002; Nieto‐Lopez and Blake 1994). Quantitative trait loci (QTL) for resistance have been located on chromosomes 1H, 2H, and 3H (Nieto‐Lopez and Blake, 1994; Raman and Read, 2000).…”
mentioning
confidence: 99%
“…Since the first report of host plant resistance to D. noxia in Triticum monococcum (Einkorn), line A 544, and other T monococcumlT durum amphiploids (du Toit & van Niekerk, 1985) many other sources of resistance have been described. The international trend for reducing the impact of D. noxia on small grains is the use of Russian wheat aphid resistant cultivars (Webster et aI., 1987;Ou Toit, 1989b;Nkongolo et at., 1991;Robinson, et at., 1992). A number of D. noxia resistant cultivars have been released for commercial use in South Africa and have been shown to have a yield advantage above susceptible cultivars in farmers fields (Marasas et aI., 1997).…”
Section: Introduction Jmentioning
confidence: 93%